King Kong (2005) [videorecording (DVD)] - Jackson, Peter, 1961-; Jackson, Peter, 1961-; Jackson, Peter, 1961-; Watts, Naomi, 1968-; Black, Jack, 1969-; Brody, Adrien; Hanks, Colin, 1977- (Universal Pictures, 2006)
Young and beautiful actress Ann Darrow is from the world of 1930s vaudeville, who is down on her luck. She meets Carl Denham, an over-ambitious filmmaker, who brings her on an exploratory expedition to a remote island where she finds compassion and the true meaning of humanity with an ape Kong. Together, beauty and beast finally meet their fate in New York, where the filmmaker has taken and displayed the ape in the quest of finding his fame by using commercial exploitation which ultimately leads to catastrophe, including the man who falls in love with Ann and plays an unlikely hero by trying to save her from Kong and her destiny.